2020
DOI: 10.1302/2046-3758.911.bjr-2020-0019.r2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of material selection on tibial post stresses in posterior-stabilized knee prosthesis

Abstract: Aims The material and design of knee components can have a considerable effect on the contact characteristics of the tibial post. This study aimed to analyze the stress distribution on the tibial post when using different grades of polyethylene for the tibial inserts. In addition, the contact properties of fixed-bearing and mobile-bearing inserts were evaluated. Methods Three different grades of polyethylene were compared in this study; conventional ultra high molecular weight polyethylene (UHMWPE), highly cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In today's society, with the aging of the population and the improvement of living standards, joint diseases have increasingly become an important factor endangering human health. Among them, knee and hip diseases, as one of the main problems affecting the quality of life and daily activities, have attracted widespread attention [1][2] . For those patients who have lost joint function due to joint diseases or serious injuries, joint prosthesis replacement surgery has become one of the key ways to restore their quality of life and mobility.…”
Section: Introductionmentioning
confidence: 99%
“…In today's society, with the aging of the population and the improvement of living standards, joint diseases have increasingly become an important factor endangering human health. Among them, knee and hip diseases, as one of the main problems affecting the quality of life and daily activities, have attracted widespread attention [1][2] . For those patients who have lost joint function due to joint diseases or serious injuries, joint prosthesis replacement surgery has become one of the key ways to restore their quality of life and mobility.…”
Section: Introductionmentioning
confidence: 99%
“…There are a considerable number of relevant factors that influence the success of total knee arthroplasty, of which the correct rotational alignment of tibial components is one of the key factors [ 4 ]. Some previous studies have reported that malposition of tibial components in the horizontal plane can be the cause of patellar complications [ 7 ], unexplained knee pain [ 6 , 17 ], knee stiffness [ 1 , 5 ], and polyethylene wear [ 9 , 14 ].…”
Section: Introductionmentioning
confidence: 99%